Isolation of segments of homologous genes with only one conserved amino acid region via PCR - Laging, Martin (Oxford University Press, 2001)
We present a method which allows the isolation of fragments from genes coding for homologous proteins via PCR when only one block of conserved amino acids is available. Sets of degenerated primers are defined by reverse translation of the conserved amino acids such that each set contains not more than 128 different sequences. The second primer binding site is provided by a special cassette that is designed such that it does not allow binding of the second primer prior to being copied by DNA synthesis. The cassette is ligated to partially-digested chromosomal DNA. The second primer is biotinylated to allow elimination of PCR products carrying degenerated primers on both sides via streptavidin binding. Fragments obtained after amplification and enrichment are cloned and sequenced. The feasibility of this method was demonstrated in a model experiment, where degenerated primers were deduced from six conserved amino acids within the family of homologs to the Escherichia coli Vsr protein.